The Analysis and Design Marketplace Information Systems Web-Based of Electronic Repair Service Providers with Haversine Method - Darmayana Putra; Benny Daniawan; Suwitno Suwitno; Andri Wijaya (bit-Tech, 2019)
This system is designed to help customers find electronic service centers were spread in Tangerang. The distribution of electronic service center makes it difficult for users to determine the right electronic service center. Sometimes customers don’t know the results of repairs from the electronic service center. Search for electronic service center on the system is using the Haversine method. Haversine is used to calculate the distance between the position of the customer and the position of the electronic service centers. In addition to Haversine, the search for electronic service center will be adjusted to the type of goods you want to repair and rating from the results of the performance electronic service center. In this system, the customer can choose the damage diagnosis available and the customer can also make a special order by describing the customer's damage. This system was tested using Black Box Testing with Boundary Value Analysis technique, based on the results of testing the system can use data with a success percentage of 96.66%. The system is tested with User Acceptance Testing to find out how much the level of user acceptance of the system designed, and the result is 75% of users agree with the system.